South Africa : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2022)
South Africa's subpar economic performance over the last decade has weakened its macroeconomic fundamentals and social indicators. In response to formidable COVID-19-related challenges, government expenditure surged, and, amid declining revenue, the budget deficit widened significantly. The South African Reserve Bank (SARB) and the Prudential Authority (PA) preserved adequate liquidity conditions and financial-sector stability. The cyclical recovery from the deep contraction has been faster than expected but its strength is unlikely to be sustained. Benign global market conditions have supported asset performance, although term premia are elevated due to fiscal risks. Bank soundness indicators remain solid, but a deepening bank-sovereign nexus raises some concerns.